Socioeconomic Status Is Associated With Antibody Levels Against Vaccine Preventable Diseases in the Netherlands - Hoes, Joske; Boef, Anna G. C.; Knol, Mirjam J.; de Melker, Hester E.; Mollema, Liesbeth; van der Klis, Fiona R. M.; Rots, Nynke Y.; van Baarle, Debbie (Frontiers in Public Health, 2018)
Background: We investigated whether low socioeconomic status (SES), which is associated with reduced health and life expectancy, might play a role in increased risk for infectious diseases. Therefore, we explored the association between SES and immunoglobulin G (IgG) levels against various pathogens. Methods: We analyzed the association between SES (educational level and net household income (NHI)) and serum IgG concentration against measles, mumps, rubella, varicella, Haemophilus influenzae type B (HiB), pneumococcus, meningococcus serogroup C (MenC), and cytomegalovirus (CMV) collected within a national cross-sectional serosurvey (2006/2007) using linear regression analyses among non-vaccinated individuals. Results: Higher educational level was associated with higher IgG concentrations against measles (GMC ratio 1.34, 95% CI 1.18-1.53) and rubella (1.13, 1.02-1.25) compared to low education level. In contrast, higher education level was associated with lower IgG concentrations against pneumococcus (0.78, 0.70-0.88), MenC (0.54, 0.44-0.68), and CMV (0.23, 0.18-0.31) compared to low education level. This pattern was also evident when NHI was used as SES indicator. Conclusion: Our study suggests that socioeconomic status is associated with antibody levels in a pathogen-dependent manner. The results suggest that differences in serological response upon infection or differences in exposure might be involved in the variation in IgG levels between SES groups.